Migration, labor, and women’s empowerment: Evidence from an agricultural value chain in Bangladesh - de Brauw, Alan; Kramer, Berber; Murphy, Mike (International Food Policy Research Institute, 2020)
As a substantial portion of the rural labor force migrates to urban areas, it is commonly assumed that women could take over traditionally male tasks in agricultural production, with potentially empowering outcomes for women. We study how changes in the supply of labor may influence female labor participation and empowerment outcomes. Using a detailed panel dataset on jute producers in Bangladesh, we test whether out-migration of household members and perceived labor shortages are associated with the share of household and hired labor performed by women, and women’s empowerment. When a household experiences reduced household or hired labor supply, we observe a relatively larger use of female household labor but not of female hired labor. We find that reduced male household labor supply is associated with improved wages mainly for male laborers, whereas reduced female household labor is associated with improved wages for male laborers and enhanced empowerment of other women in the household. These findings suggest that given existing gender norms, male and female labor are not perfect substitutes for one another, and as a result, male outmigration is not associated with improved outcomes for women in cash crop production. Our results demonstrate a need for better understanding of the role of gender in rural labor markets, particularly in contexts of rapid urbanization.